Fundamental Analysis, Technical Analysis and Broker Summary Analysis in Investing in Indonesian Stock Market - Alvin Raditya alvin; Erman Arif Sumirat erman (Publikasi Indonesia, 2022)
Investors, particularly beginner investors, are still uncertain about which stock to buy and when is the best moment to buy or sell the stock when they first begin investing in the capital market. Analysis is thus required to address the major issue so that investors do not select the incorrect stock and the incorrect moment to purchase or sell it. In order to derive financial ratios, fundamental analysis uses the company's financial statements. The results of the fundamental analysis will reveal whether or not the firm is doing well. However, technical analysis aids in determining when it is best to purchase or sell a stock. The broker summary analysis is an additional analysis that may be utilized in addition to these two that are both very often employed. It may be inferred from this report if the broker is stockpiling or dispersing goods.When performing fundamental research, a stock screener is utilized to calculate the ratios of Return on Assets, Return on Equity, Price to Book Value, Price to Earnings Ratio, and Earnings per Share. The Moving Average approach uses a Simple Moving Average, a Weighted Moving Average, and an Exponential Moving Average to establish the selling and purchasing locations. statistics on stocks from 2016 until 2022. The highest rate of return when using the Simple Moving Average approach is 112.03 percent.